Simultaneous determination of nirmatrelvir and ritonavir in human plasma using LC–MS/MS and its pharmacokinetic application in healthy Chinese volunteers. (5th August 2022) - Liu, Chenxi; Zhu, Miqun; Cao, Liyun; Boucetta, Hamza; Song, Min; Hang, Taijun; Lu, Yuting
Abstract: Paxlovid, a copackaged medication of nirmatrelvir tablets (150 mg) and ritonavir tablets (100 mg) developed by Pfizer, is one of the first orally accessible COVID‐19 antiviral medicines to be approved for emergency usage. In this research, an efficient LC–MS/MS method for simultaneous determination of nirmatrelvir and ritonavir in human plasma was established and validated with remdesivir as an internal standard. Chromatographic separations were carried out on a Thermo BDS Hypersil C18 column (4.6 × 100 mm, 2.4 μm) using deionized water and methanol as mobile phase, both added with 0.1% (v/v) formic acid. Based on the positive electrospray ionization mode, nirmatrelvir and ritonavir were analyzed by selective reaction monitoring. Excellent precision, accuracy, recovery, and linearity were demonstrated, covering the range of 50–5000 ng/mL for nirmatrelvir and 10–1000 ng/mL for ritonavir. Then, the established method was used for determining the pharmacokinetic profile of Paxlovid in healthy Chinese volunteers. The pharmacokinetic parameters, including C max, T max, t 1/2, and AUC0 − ∞ of Western volunteers, correspond well with the results of this pharmacokinetic investigation.